The Agribusiness Innovation Center of Senegal : Scaling a Competitive Horticulture Sector through Value Adding Post-Harvest Processing - Brethenoux, Julia; Dioh, Simon; Drago, Nicola; Giddings, Steven; Olafsen, Ellen; Thaller, Jim (World Bank, Washington, DC, 2014)
Senegal has tremendous potential to raise incomes and create jobs in agriculture. This potential is particularly strong in the horticulture sector where Senegal enjoys a comparative advantage because of the following factors: favorable climatic and water conditions; capacity to supply European markets at a time when others cannot; proximity to European markets with availability of competitive air and sea transport; access to quality inputs; and few policy distortions. The fact that exports have increased from 2,700 tons in 1991 to 51,270 tons in 2011 indicates the quality and demand for Senegalese horticulture products. However, only about 5 percent of the fruits and vegetables grown in Senegal are processed. The country imports many processed products that could be produced competitively domestically, and exports raw materials that, if processed, could be sold at much higher margins. Processing could also help reduce post-harvest losses, which dramatically affect farmers' incomes. The country is, therefore, not realizing the income and job generating potential offered by its comparative advantage. This document proposes a new model for promoting the growth of a competitive value adding horticulture sector in Senegal. The Agribusiness Innovation Center (AIC) will provide a set of financial and nonfinancial services to high-growth potential entrepreneurs, aiming to accelerate the growth of their enterprises and demonstrating product, process, and business model innovation across the horticulture sector. AIC complements existing efforts focused on farm-level improvements and foreign investment facilitation.